Operationalising the countercyclical capital buffer: indicator selection, threshold identification and calibration options - Carsten Detken; Olaf Weeken; Lucia Alessi; Diana Bonfim; Miguel M. Boucinha; Christian Castro; Sebastian Frontczak; Gaston Giordana; Julia Giese; Nadya Jahn; Jan Kakes; Benjamin Klaus; et al. (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2014)
This paper presents the analysis underpinning the ESRB Recommendation on guidance on setting countercyclical buffer rates (ESRB 2014/1). The Recommendation is designed to help authorities tasked with setting the countercyclical capital buffer (CCB) to operationalise this new macroprudential instrument. It follows on from the EU prudential rules for the banking system that came into effect on 1 January 2014.
Keywords: G21; G28; E58; 330; countercyclical capital buffer; banking regulation; systemic risk